418 Ultrasound molecular imaging of the role of von willebrand factor-mediated platelet adhesion in atherogenesis. (17th January 2020) - Ozawa, K; Muller, M; Varlamov, O; Packwood, W; Xie, A; Lopez, J A; Lindner, J R
Abstract: Funding Acknowledgements: JSPS Overseas Research Fellowship Background: Platelets are known to be both pro-inflammatory and pro-mitogenic. However, the role of platelet-endothelial interactions in the initiation and growth of atherosclerotic lesions is not well understood. Purpose: We used contrast-enhanced ultrasound (CEU) molecular imaging of the arterial endothelium to test the hypothesis that platelet attachment to endothelial Von Willebrand Factor (VWF) promotes atherogenesis. Methods: We studied wild-type mice (WT), low-density lipoprotein deficient mice fed western diet to produce atherosclerosis (LDLR-/-), and LDLR-/- mice also deficient for ADAMTS-13 (LDLR-/-ADAMTS13-/-) which is the enzyme responsible for proteolytic cleavage of endothelial-associated VWF. Mice were studied at 20 weeks and 30 weeks of age. A subset of LDLR-/- mice were treated with recombinant ADAMTS13 1 hr prior to study. Proximal aortic CEU molecular imaging of P-selectin, vascular cell adhesion molecule (VCAM)-1, von Willebrand factor (VWF), and platelet GPIbα was performed. Aortic distensibility was assessed using high-frequency (30 MHz) transthoracic echocardiography and tail cuff blood pressure systems. NF-κB of aorta was assessed by ELISA kit. Plaque size and composition were assessed by histology. Platelets and macrophage immunohistochemistry were also performed on confocal microscopy. Results: Aortic molecular imaging signal for P-selectin, VCAM-1, VWF, and platelet adhesion was significantly higher in LDLR-/- than WT mice, and increased by 2-fold between 20 and 30 wks of age. Signal for VWF and platelet adhesion was abolished 1 h after administration of ADAMTS13, confirming that platelet adhesion was VWF-mediated. At 20 and 30 wks of age, molecular imaging signal for all targets was 2-fold higher (p < 0.01) in LDLR-/-ADAMTS13-/- versus LDLR-/- mice. The LDLR-/-ADAMTS13-/- mice also had lower aortic distensibility (p < 0.05), had a 2-fold higher NF-κB signal (p < 0.05), and had a 2-fold greater total plaque area (p < 0.01). Fluorescent immunohistochemistry confirmed that the LDLR-/-ADAMTS13-/- mice also had greater platelets (p < 0.05) and increased macrophage content (p < 0.05) than LDLR-/- mice in aortic plaque. Conclusion: In early to mid-stage atherosclerosis, abnormal regulation of endothelial-associated VWF results in platelet adhesion and secondary up-regulation of endothelial inﬂammatory adhesion molecules, thereby promoting atherosclerotic plaque progression. These results indicate an important role of platelet-endothelial interactions in early atherogenesis.